CHARACTER EDUCATION IN MANTRA YOGA: Case Study of STAHN Mpu Kuturan Singaraja Yoga Student Activity Unit - I Made Ariasa Giri (International Journal of Interreligious and Intercultural Studies, 2025)
Character is basic of education, the aim of national education is to create people who are capable, skilled, have character and have faith in God Almighty. A religious approach can help realize student character, because religion teaches managing feelings. The mind has a role in managing feelings, therefore techniques are needed to manage the mind, one of which is mantra yoga. The aim of this research is to describe character education in mantra yoga. Mantra yoga is a means of introducing yoga asana and meditation at STAHN Mpu Kuturan Singaraja, there are several mantras used, namely, Gayatri mantra, guru mantra, Patañjali Dhyana, mantra accompanying surya namaskara, and Mahamrityunjaya mantra. Mantra has a very effective function in helping students connect with themselves so that they can maximize the student's potential and talents. Mantra yoga has a calming effect on the mind thereby providing health benefits, emotional control and creativity.